Revealing Unconscious Consumer Reactions to Advertisements That Include Visual Metaphors. A Neurophysiological Experiment - García-Madariaga, Jesús; Moya, Ingrit; Recuero, Nuria; Blasco, María-Francisca (Frontiers in Psychology, 2020)
The main challenge of advertising is to catch consumers’ attention and evoke in them positive attitudes to consequently achieve product preference and higher purchase intentions. In modern advertising, visual metaphors are widely used due to their effects such as improving the advertising recall, enhancing persuasiveness and generating consumers' positive attitudes. Previous research has pointed out the existence of an "inverted U-curve” that describes a positive relationship between the conceptual complexity of metaphors and consumers’ positive reactions to them, which ends where complexity outweighs comprehension. Despite the dominance of visual metaphors in modern advertising, academic research on this topic has been relatively sparse. The inverted U-curve pattern has been validated regarding ad appreciation, ad liking, and purchase intention by using declarative methods. However, at present, there is no evidence of consumers’ neurophysiological responses to visual metaphors included in advertising. In view of this gap, the aim of this research is to assess consumer neurophysiological responses to print advertisements that include visual metaphors, using neuroscience-based techniques. 43 participants were exposed to 28 stimuli according to three levels of visual complexity, while their reactions were recorded with Electroencephalogram (EEG), Eye-tracking (ET), and Galvanic Skin Response (GSR). The results indicated that, regardless of metaphor type, ads with metaphors evoke more positive reactions than non-metaphor ads. EEG results revealed a positive relationship between cognitive load and conceptual complexity that is not mediated by comprehension. This suggests that the cognitive load index could be a suitable indicator of complexity, as it reflects the amount of cognitive resources needed to process stimuli. ET results showed significant differences in the time dedicated to exploring the ads, however, comprehension doesn’t mediate this relationship. Moreover, no cognitive load was detected from GSR. ET and GSR results suggest that neither methodology is a suitable measure of cognitive load in the case of visual metaphors. Instead, it seems that they are more related to the attention devoted to the stimuli. Our empirical analysis reveals the importance of using neurophysiological measures to analyze the appropriate use of visual metaphors and to find out how to maximize their impact on advertising effectiveness.